Pengaruh Perubahan Iklim Terhadap Produksi Perikanan Tangkap di Laut Jawa Timur Indonesia - Rhochmad Wahyu Illahi; Ali Fahmi Syahputra; Gilang Rusrita Aida; Choirunnisa Nur Prajasti (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2023)
East Java Province has the potential for a large capture fisheries industry which is supported by its strategic location because it is bordered by the Java Sea, Bali Strait, and the Indian Ocean. The existence of climate change is allegedly having a direct or indirect impact on capture fisheries. Climate change causes an increase in sea surface temperatures, an increase in extreme weather events and their intensity, changes in precipitation patterns, and freshwater runoff. Based on this, it is necessary to carry out an analysis to determine the effect of temperature (X1), rainfall (X2), humidity (X3), and sunlight (X4) simultaneously and partially on fish production in East Java Province, Indonesia. This research method is descriptive using multiple linear regression analysis, F test, and t-test. The results showed that the data were normally distributed and there was no multicollinearity in the independent variables. The resulting linear regression equation is y= -1775919,888 + 21619,513X1 – 160,916X2 + 30558,699X3 – 4664,191X4. The results of the F test show a significant value of 0.000, which means 0.000 <0.05 so all independent variables have a significant effect simultaneously on the dependent variable. The t-test shows that the temperature (X1) and solar radiation (X4) has no partially significant effect on the dependent variable. While the variables humidity (X2) and rainfall (X3) have no partial significant effect on the dependent variable, namely capture fisheries production.